Keloids and inflammation: the crucial role of IL-33 in epidermal changes - Chen, ZongAn; Yang, YaTing; Wang, XiuXia; Xia, LingLing; Wang, WenBo; Wu, XiaoLi; Gao, Zhen (Frontiers in Immunology, 2025)
IntroductionKeloids are benign fibroproliferative disorders characterized by excessive collagen deposition and inflammation that extend beyond the original wound boundaries. IL-33 is an alarmin cytokine released upon cellular damage or stress. Dysregulation of IL-33 in epidermal keratinocytes compromises the skin barrier and triggers chronic inflammation.MethodIn this study, we first noticed an increased expression of IL-33 in the keratinocytes of keloid epidermis through histological staining. Then, an increased expression of IL-33 receptor (ST2) in the lymphocytes infiltrating the superficial dermis of keloid scars were identified through histological staining and flow cytometry analysis. The IFN-γ-IL-33 loop between lymphocytes and keratinocytes were further revealed by flow cytometry and Western blotting analysis. The abnormal keratinocyte differentiation in epiderm is mediated by IFN-γ-IL-33 loop were confirmed by in vitro studies in HaCaT cells via Western blotting analysis and immunofluorescence staining. Finally, the IFN-γ-IL-33 loop were also verified in cocultured peripheral blood mononuclear cells and HaCaT through ELISA analysis.ResultsOur results demonstrate that IL-33 levels are significantly elevated in the epidermis of keloid tissues, where it functions as an alarmin, promoting a chronic inflammatory response. We further reveal a feedback loop between IL-33 and interferon-gamma (IFN-γ), whereby IL-33 induces IFN-g production in lymphocytes, which in turn stimulates keratinocytes to produce more IL-33. This loop contributes to impaired keratinocyte differentiation and skin barrier dysfunction, exacerbating the inflammatory environment. DiscussionBy elucidating the role of the IL-33/ST2 axis in keloid formation, this research provides valuable insights into potential therapeutic targets for managing this challenging condition.